1998
DOI: 10.1021/cm970340s
|View full text |Cite
|
Sign up to set email alerts
|

Silylated Coumarin Dyes in Sol−Gel Hosts. 2. Photostability and Sol−Gel Processing

Abstract: The photostability characteristics of numerous silylated coumarin dyes within SiO 2 xerogels and SiO 2 :PDMS Polyceram films, and of neat silylated coumarin dye films have been determined and related to the sol-gel processing conditions and host composition. FTIR spectroscopy was used to monitor the hydrolysis reaction rates of the silylated dyes and other Si-alkoxide precursors. The silylated dyes had varying reaction rates depending on the degree of functionality and the linkage between the alkoxide and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 28 publications
3
48
0
2
Order By: Relevance
“…Q peaks represents a quaternary oxygen tetrahedron and the superscripts denote the numbers of alkoxide or Si-OH groups that have reacted to form Si-O-Si linkages (Suratwala et al 1998). The chemical shifts of the Q peaks were identified by their relative positions and by assigned peak values from the literature (Engelhardt & Michel 1987).…”
Section: Cp Mas 29 Si Nmr Spectroscopymentioning
confidence: 99%
“…Q peaks represents a quaternary oxygen tetrahedron and the superscripts denote the numbers of alkoxide or Si-OH groups that have reacted to form Si-O-Si linkages (Suratwala et al 1998). The chemical shifts of the Q peaks were identified by their relative positions and by assigned peak values from the literature (Engelhardt & Michel 1987).…”
Section: Cp Mas 29 Si Nmr Spectroscopymentioning
confidence: 99%
“…Incorporation of organic molecules such as dyes inside solid matrices is an attractive topic of research because of the photostability and fluorescence quantum yield [1][2][3] of the modified materials. An approach in this regard is to incorporate molecules inside silica spheres, 4,5 the advantage of this kind of nanoscopic containers is that they can be used to control the environment of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…elimination of translational freedom by avoiding inter-molecular interaction, immunization of optical properties from high concentration interferences, reduction in rotational relaxation of the excited state of laser dyes, elimination of inherent problems with physical pumping, ease of use and replacement, and fabrication of samples in the desired form and shape. 1 Amongst the several investigated organic dye doped ORMOSILs, [4][5][6][7][8][9][10][11][12] the chemical bonded SiO 2 -PDMS ORMOSIL is noted as a useful host-matrix for doping a dye. A detailed investigation on the SiO 2 -PDMS ORMOSIL has already been carried out in the present laboratory because the tetraethoxysilane (TEOS, an inorganic precursor for SiO 2 ) shows a controllable hydrolysis reaction rate and PDMS (poly(dimethylsiloxane)) possesses specific properties like transparency, hydrophobicity, good chemical and thermal stability and similarity of its backbone structure (-Si-O-) to that of TEOS.…”
Section: Introductionmentioning
confidence: 99%
“…15 Coumarin 4 was chosen as a organic dye because of its high fluorescence efficiency, chemical-and photo-stability. [7][8][9] It also exhibits specific molecular species associated with protonation-deprotanation reactions. [7][8][9] It was observed that the increase in the acid or base concentration increased the photo-luminescence peak intensity, which was attributed to an increase in the interaction between the gel matrix and the dye molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation